Effects of Relative Inertial Load on Quadriceps Electromyography during Maximal Effort Flywheel-based Iso-Inertial Training (FIT) Squats - Bollinger Lance (International Universities Strength and Conditioning Association, 2022)
The effects of inertial load on quadriceps electromyography (EMG) during flywheel-based iso-inertial training (FIT) squats is unclear. Healthy, resistance-trained males (n=8) and females (n=8) completed five sets of five maximal-effort squats with varying inertial loads in a randomized order.  Sagittal plane knee joint angles and surface EMG activity of the vastus lateralis (VL) were measured. Average knee angular velocity, but not peak knee flexion or total excursion, decreased during both the concentric and eccentric phases with increasing inertial load (p<0.001) in both sexes.  Integrated EMG (iEMG) activity increased with increasing inertial load for all muscles (p<0.001).  VL iEMG and peak amplitude were significantly greater in females.  However, peak EMG amplitude was not significantly different among inertial loads for either sex. Mean EMG amplitude during the concentric phase and eccentric phases of the VL tended to be greater in females.  Increasing relative inertial load increases quadriceps iEMG activity due to greater exercise duration, but has minimal effects on EMG amplitude.